About the scope and format of the "Ukrainian conflict" - Kobaliya, Dmytro (Skhid, 2015)
The article is devoted to the definition of the format and scope of the "Ukrainian conflict". The paper emphasizes that the most accurate notion in relation to Ukrainian events 2014-2015 is the "conflict" and, therefore, it’ possible participants are examined. The author concludes that the events of the "Maydan" were largely provoked from outside and their main goal was to create a precedent of the violation of the Constitution of Ukraine as a pretext for the beginning of the dissolution of the country. The failure of these plans transforms the conflict into an open one, making the Russian Federation and Ukraine its real subjects. The inability of Russia to hide its involvement in the conflict is due to factors such as: over-valuation of cultural conflict between East and West Ukraine, unreasonable reliance on the loyalty of the West European countries and underestimating of the degree of the development of Ukrainian society. The paper raises the question whether the "Ukrainian conflict" is the planned takeover attempt by Russia of the Ukrainian territory or is it only a precedent for global political transformations in the world.